h-6u+7=-29

Simple and best practice solution for h-6u+7=-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h-6u+7=-29 equation:


Simplifying
h + -6u + 7 = -29

Reorder the terms:
7 + h + -6u = -29

Solving
7 + h + -6u = -29

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + h + -7 + -6u = -29 + -7

Reorder the terms:
7 + -7 + h + -6u = -29 + -7

Combine like terms: 7 + -7 = 0
0 + h + -6u = -29 + -7
h + -6u = -29 + -7

Combine like terms: -29 + -7 = -36
h + -6u = -36

Add '6u' to each side of the equation.
h + -6u + 6u = -36 + 6u

Combine like terms: -6u + 6u = 0
h + 0 = -36 + 6u
h = -36 + 6u

Simplifying
h = -36 + 6u

See similar equations:

| 6=2k-8k | | E(x)=0.0048x^3-0.0054x^2 | | 7(x-6)=5(x+2) | | 6b^2=42b-72 | | 7(8-9x)=0 | | 3x+9-5x+7-2x=20 | | 7y+45=y-3 | | -x+21=x+9 | | a-17=48 | | 3b-3=9 | | (4x+8)-(2x+4)=2x | | 2x+5(5x-1)=-113 | | 10(c-7)=-36 | | 7/9-= | | 5y/9=45 | | (4x+6)-(2x+4)=2x | | 9x(x+9x)= | | -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 |

Equations solver categories